How Is Individuality Possible? Georg Simmel’s Philosophy and Sociology of Individualism - Müller, Hans-Peter; Cavalli, Alessandro; Ferrara, Alessandro (Simmel Studies, 2018)
“How is society possible?” The mirror image of Simmel’s famous question is: “How is individuality possible?” To answer this question Simmel developed a philosophy and sociology of individualism. The “tragedy of individuality” consists of the hiatus between the social structure offering freedom and individuality and the culture unable to provide the necessary meaning and orientation. This is shown with respect to epistemic, structural, cultural and ethic individuality.